The efficacy of platelet-rich plasma applicated in spinal fusion surgery: A meta-analysis - Yu, Hongwei; Zhou, Zhaohong; Yu, Bin; Sun, Tianwei; Tang, Qiong; Jia, Yutao (Frontiers in Surgery, 2022)
Objective The purpose of this meta-analysis is to evaluate the effect of the application of platelet-rich plasma (PRP) in spinal fusion surgery on the fusion rate of the spine. Methods A comprehensive search of the PubMed, Embase, Cochrane Library, and Science Direct databases was conducted to identify randomized control trials (RCTs) or observational cohort studies that evaluated the efficacy and safety of PRP in spinal fusion. Data on final fusion rate, changes in the visual analog scale (VAS), estimated blood loss (EBL), and operative time was collected from the eligible studies for meta-analysis. Patients were divided into PRP and non-PRP groups according to whether PRP was used during the spinal fusion procedure. Results According to the selection criteria, 4 randomized controlled trials and 8 cohort studies with 833 patients and 918 levels were included. The outcomes indicated that PRP application is associated with a lower fusion rat (OR = 0.62, 95% CI: (0.43, 0.89), P = 0.009) at final follow-up (>24 months). Subgroup analysis showed a lower rate of spinal fusion in the PRP group compared to the non-PRP group (OR = 0.35, 95% CI: (0.21, 0.58), P < 0.001) when spinal fusion was assessed using only anterior-posterior radiographs. When the bone graft material was a combination of autologous bone + artificial bone, the spinal fusion rate was lower in the PRP group than in the non-PRP group (OR = 0.34, 95% CI: (0.16, 0.71), P = 0.004). The PRP and non-PRP groups showed no significant differences in VAS changes at the 24th postoperative month (WMD = 0.36, 95% CI: (−0.37, 1.09), P = 0.33); Application of PRP does not reduce the estimated blood loss (WMD = −86.03, 95% CI: (−188.23, 16.17), P = 0.10). In terms of operation time, using PRP does not prolong operation time (WMD = −3.74, 95% CI: (−20.53, 13.04), P = 0.66). Conclusion Compared with bone graft fusion alone, PRP cannot increase the rate of spinal fusion. Inappropriate methods of spinal fusion assessment or mixing PRP with artificial/allograft bone may have been responsible for the lower rate of spinal fusion in the PRP group. Systematic Review Registration doi: 10.37766/inplasy2022.5.0055